2020
DOI: 10.1002/jgm.3266
|View full text |Cite
|
Sign up to set email alerts
|

Variants in multiple genes are associated with esophageal cancer risk in a Chinese Han population: A case–control study

Abstract: Background: The present study investigated whether 16 single nucleotide polymorphisms (SNPs), selected based on minor allele frequencies, Hardy-Weinberg equilibrium and reported SNPs related to the susceptibility of certain gastrointestinal cancer, were associated with esophageal cancer (EC) risk in a Chinese Han population. Methods: We genotyped 16 SNPs among 506 cases and 507 controls using Agena MassARRAY (Agena, San Diego, CA, USA). The association between 16 SNPs and EC risk was analyzed by a chi-squared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…SEMA5B is a constituent of the semaphorins, a cohort of soluble proteins known for orchestrating cellular differentiation, morphology, functionality, and intercellular communications. Its pivotal function extends to the modulation of tumor proliferation, dissemination, along with its involvement in bone metastasis and disorders affecting microvasculature ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…SEMA5B is a constituent of the semaphorins, a cohort of soluble proteins known for orchestrating cellular differentiation, morphology, functionality, and intercellular communications. Its pivotal function extends to the modulation of tumor proliferation, dissemination, along with its involvement in bone metastasis and disorders affecting microvasculature ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have strongly demonstrated that specific genes, such as oncogenes and tumor suppressor genes, are risk factors for certain malignancies (Khan et al, 2018;Elek et al, 2020;Shareefi et al, 2020;Vysotskaia et al, 2020;Xiong et al, 2020). Oncogenes can promote tumor growth when they are activated, whereas tumor suppressor genes hinder tumor growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that certain genes, such as oncogenes and tumor suppressor genes, are risk factors for many types of cancer (20)(21)(22)(23)(24). When activated, oncogenes stimulate tumor growth whereas tumor suppressor genes prevent tumor growth and development.…”
Section: Introductionmentioning
confidence: 99%